Power System Protection Coordination Studies at Gas Processing Plant B (GPPB), PETRONAS Gas Berhad (PGB), Paka - HARUN, SITI FATHIMAH (Universiti Teknologi PETRONAS, 2009)
Power system protection coordination is a study on protection for power system from any fault such as overcurrent, earthfaulth or any abnormal system operating condition that can cause failure to the systems component for example transformer, generator and transmission line. If any faults occur, the protection devices will recognize faults and initiate action to clear the fault from the system. In Gas Processing Plant B (GPPB), the protection system is an important part to take care but sometimes for some reason, the protection system is not work as what we want, therefore the studies on this project will be help the company to improve the current protection systems. This study is based on some characteristics in power system protection and develops the current power system protection coordination for Gas Processing Plant B (GPPB). With this new protection system coordination, the author hopes to help the company to improve the current protection systems.